KESALAHAN STRUKTUR TEKS DAN KEBAHASAAN LAPORAN HASIL OBSERVASI: STUDI KASUS DI SMP KRISTEN 1 SURAKARTA - Dwi Sarwindah; Sumarwati Sumarwati; Slamet Mulyono (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2019)
This study aims to describe the structural error of the text and language of the observation report of the seventh grade students of SMP Kristen 1 Surakarta. This study is a qualitative descriptive study with a sample of observational reports from students of SMP Kristen 1 Surakarta. The sampling technique used was purposive sampling.Data collection techniques used were document analysis and in-depth interviews. The analysis technique used is flow analysis because the data analyzed is unchanging, which includes data reduction, data presentation, conclusion drawing. The conclusions of this study are as follows. The first mistakes found in student corals include text structure errors, paragraph errors, sentence errors, word choice errors, and spelling mistakes. The two errors that occur in the student observation report are due to several factors including: lack of writing practice, lack of interest in reading, lack of understanding of the rules of writing in Indonesian.